Policies for young adults with reduced work capacity: Labour market impact in Sweden and Norway - Caroline King Barnard Hall; Inés Hardoy; Kristine Von Simson (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2022)
The rising numbers of young people with disability pension concerns many advanced economies. We present results from a comparative analysis of Sweden and Norway, two countries which are very similar in many respects, but differ regarding the policy mix to enhance the employability of the work disabled. Using rich longitudinal data, we follow unemployed young adults (aged 25- 29 years old) with reduced work capacity to investigate the effect of different types of labour market policies. We follow these individuals up to four years after the start of unemployment. Our results indicate that, in spite of radical differences in programme composition and strategies, there are surprisingly small country differences in impacts. Having participated in workplace related programmes about doubles the likelihood of entering regular employment or education. Participating in qualifying training courses also increases this likelihood, but effect sizes are smaller.
Keywords: J08; J64; J68; 330; Unemployment; labour market programmes; reduced work capacity; young adults